Efforts to Increase the Power Seed Germinantion of Andaliman (Zanthoxylum acanthopodium DC) with Cemical Scarification using Sulfuric Acid (H2SO4) - Shofyani, Enda; Sujarwati, Sujarwati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Zanthoxylum acanthopodium DC. Belongs to the Rutaceae family commonly used for cooking spices and medicinal plants and has the potential to be developed in the pharmaceutical and food industries. Publication on aspects of cultivation is still limited, and generative propagation using seeds is still a problem because the seeds have low seed germination. This happens because the seeds experience dormancy and have a hard seed coat structure. This research aims to know the effect of H2SO4 concentration and soaking time, and the interaction of both factors on Z.acanthopodium seed germination, and determine the optimal concentration of H2SO4 and soaking time to increase the germination of Z. acanthopodium seed. This study used a Factorial Completely Randomized Design with two factors. The first factor is the concentration of H2SO4 0, 25, 50, 75, and 100%, and the second factor is the soaking time of 15, 30, 45, and 60 minutes followed by soaking in water for 24 hours. The parameters observed were the percentage of germination, germination time, and vigor index. The observation data obtained were discussed descriptively. The results showed that the treatment of seeds soaking in H2SO4 at concentrations of 0%, 25%, 50%, 75%, and 100% with a soaking time of 15 minutes, 30 minutes, 45 minutes, and 60 minutes was not able to increase the germination power of andaliman seeds Z. acanthopodium. Soaking seeds in 75% H2SO4 for 60 minutes resulted in a germination percentage of 6.67%, a germination time of 7 days, and a vigor index of 0.05 seeds /day.